Food structure design to modulate bioaccessibility of carotenoids from brazilian native fruits after screening of eleven non-conventional tropical fruits - Berni, Paulo Roberto de Araujo (2018)
Brazil is the country with the greatest biodiversity on the planet and a major producer of food. Tropical fruits, especially natives from Brazil, may contain considerable amounts of carotenoids that have antioxidant, anti-inflammatory, provitamin A and anticancer actions, such as β-carotene and lycopene. The food structure design concept aims to manipulate the food matrix for specific purposes, e.g. the preservation and manipulation of carotenoid bioaccessibility. The aim of this thesis was to explore tropical fruits, native and exotic from Brazil in the development of delivery systems for carotenoids. A screening step was carried out with 11 fruits, among which 2 were selected, the pitanga (Eugenia uniflora) and buriti (Mauritia flexuosa) fruits that were used for the production of microemulsions. At the screening were evaluated the proximate composition, fiber contents, carotenoid profiles and bioacessibilities. The nutritional value demonstrated that these fruits have high potential as raw-materials for healthy products due to their high fiber, minerals and carotenoid contents in addition to low energy value. Analysis by HPLC-DAD allowed the identification of 14 carotenoids in the 11 fruits studied for the screening. Results demonstrated the superiority of the bioaccessibility of xanthophylls (ranging 10 % - 52 %) in relation to carotenes, and the low bioaccessibility of lycopene from pitanga (1.1 %) and average bioaccessibility of β-carotene from buriti (26 %). Pitanga and buriti had their carotenoid profiles analyzed and monitored throughout an in vitro simulation of the digestion coupled with caco-2 cell cultures. Although xanthophylls are more bioaccessible, the intestinal ephitelium absorb preferentially the provitamin A carotenoids, such β-carotene and β-criptoxanthin. In order to produce these microemulsions, high-speed homogenization (HSH) and ultrasound (US) were studied in combination with the use of surfactants (Whey Protein Isolate and Tween 80), and addition of corn oil as carotenoid carrier. The experiments have shown that the interaction of US and HSH is capable to break cell walls and release carotenoids with higher efficiency. Optical and fluorescence microscopy, as well as carotenoid analysis demonstrated that it was possible to manipulate the food matrix structure releasing the carotenoids from the plant cells and encapsulating them inside the oil droplets, what increased their retention after processing. The microemulsion were affected by time of processing and by surfactant related to their rheology, final structure, stability of emulsion and carotenoid stability to processing. Finally, a dynamic gastrointestinal system was used to compare the behavior of carotenoids from whole fruit pulps and selected microemulsions (2% Tween 80, 5% corn oil, processed by HSH-US 4 min -4 min). The results demonstrated that it was possible to increase the stability to digestion and bioaccessibility of total carotenoids, lycopene and β-carotene from the microemulsions.